ASSOCIATION OF OCCUPATIONAL STRESS WITH OBESITY, SLEEP QUALITY, AND PHYSICAL ACTIVITY LEVEL IN INDUSTRIAL SECTOR WORKERS (CIPEEX, 2025)
Stress negatively impacts physical and mental health, contributing to obesity, sleep disorders, and sedentary behavior. Obesity, associated with chronic diseases such as diabetes and hypertension, is a public health problem. Regular physical activities help reduce stress and improve overall health, while poor sleep quality is linked to various health issues. The study evaluated the perception of stress and its relationship with obesity, sleep, and physical activity in 158 workers from a company producing thermal insulation solutions. The results showed that individuals with low stress practice on average 123 minutes of physical activity per week and sleep 7.0 hours per night, while those with high stress practice on average 58.3 minutes of physical activity per week and sleep 6.3 hours per night, highlighting the importance of promoting physical exercise and good sleep quality to reduce stress and improve health.
Keywords: stress; obesity; sleep; physical activity